2021
DOI: 10.1055/a-1525-2131
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Dopamine Agonist-Resistant and Aggressive Prolactinomas: A Comprehensive Analysis of the Literature

Abstract: Despite most of the prolactinomas can be treated with endocrine therapy and/or surgery, a significant percentage of these tumors can be resistant to endocrine treatments and/or recur with prominent invasion into the surrounding anatomical structures. Hence, clinical, pathological, and molecular definitions of aggressive prolactinomas are important to guide for classical and novel treatment modalities. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…The Ki-67 antigen is a protein used as a proliferation marker for human tumour cells. Refractory prolactinomas often show aggressive features and tend to exert higher angiogenesis, cell proliferation, and atypia [ 10 , 20 , 23 , 25 ]. Moreover, the presence of genetic predisposition indicates a poorer prognosis [ 19 , 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Ki-67 antigen is a protein used as a proliferation marker for human tumour cells. Refractory prolactinomas often show aggressive features and tend to exert higher angiogenesis, cell proliferation, and atypia [ 10 , 20 , 23 , 25 ]. Moreover, the presence of genetic predisposition indicates a poorer prognosis [ 19 , 20 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another treatment approach is a stepwise dose escalation beyond conventional doses to the maximally efficient and tolerated dose, as long as the patient responds with some reduction in PRL level to every dose adjustment [ 10 , 16 , 18 ]. It has been reported that 10–20% of the patients require higher than recommended doses of DA to achieve normoprolactinaemia and that DA resistance can be overcome by escalating the dose to a maximal tolerable dose in 75% of the patients [ 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations